Relationships between nutrientsupply, genotype and some physiological properties of winter wheat - Szabó, Éva; Pepó, Péter (Acta Agraria Debreceniensis, 2012)
The chlorophyll content (SPAD), leaf area index (LAI) and leaf area duration (LAD) of three winter wheat varieties have been investigated on a chernozem soil. Three winter wheat varieties (GK Öthalom, Pannonikus and Genius) in three different nutrient-supply levels have been involved in our experiment in the crop-year of 2010/2011. The investigated physiological properties have been set against to the yield results. Upon the results of this comparison it has been stated that there is a close relationship between the investigated physiological properties and yield averages. The SPAD-values showed a growing tendency parallel to the growth of the nutrient-supply levels. The varieties have the highest SPAD-values at the nutri ent-level of N120+PK. Compared to the yield averages we have stated that varieties that have higher SPAD-values have realized higher yields as well. Higher nutrient dosages have increased in the leaf area. In case of all the three varieties the highest LAI-values were measured at the flowering stage (23. 05.) in the treatment whit N120+PK. Varieties with higher leaf area have produced higher yields as well. Parallel to the increasing nutrient-supply levels the value of leaf area duration increased as well. We measured the highest LAD-values in the treatment of N120+PK nutrient-level. By the LAD-values it can be stated that more durable and larger leaf area has been produced in the flowering and ripening phenophases, due to the higher nutrient-dosages. Analysing the relationships between the results it can be stated that there is a strong positive relationship between fertilizer treatments and SPAD-, LAI- and LAD-values. The genotype showed a strong positive correlation to SPAD-values. Yield averages showed strong positive correlation to SPAD-, LAI- and LAD-values as well.